INTERDISCIPLINARY REMOTE DIDACTIC LABORATORY “G.SAVASTANO”: PHYSICS APPLICATION - Apergis, A.; Rapuano, S.; Zoino, F. (International Journal of Computing, 2014)
E-learning offers to the student’s didactic tools and course materials over Internet. By distributing tools and materials in this fashion, students isolated from the University environment can still obtain University degrees in many fields. Courses that include laboratory sessions have traditionally required students to be on-site. This is primarily due to the need for laboratory resources to be located in a single site for both practical and safety reasons. This fact hampered the freedom of non traditional (off campus) students to achieve their educational goals. The web adaptations of software packages such as LabVIEW allow control of experiments over Internet. Remote laboratories then become possible. In this framework the Remote Laboratory Distributed on Geographical Network LA.DI.RE. “G.Savastano” of University of Sannio [1] was born, with the aim of developing a virtual learning environment to deliver, through the distance learning methodologies, theoretical lessons as well as laboratory activity on real measurement instrumentation. The paper highlights the interdisciplinary aspect of LA.DI.RE. “G. Savastano”, showing the possibility to provide different real experiments independent of software development environment, thanks to use of an open Learning Management System (LMS) and concerning different didactic fields. In this case the authors present a physics experiment representing a practical session within a Physics course realized in collaboration by researchers of the University of Sannio, in Italy, and University of Thessaloniki in Greece.